2017
DOI: 10.4236/ce.2017.88091
|View full text |Cite
|
Sign up to set email alerts
|

Adoptability of Peer Assessment in ESL Classroom

Abstract: In ESL class, a teacher in charge of the class usually evaluates all the students' performances, where using peer assessment may be a good way to confirm or modify the teacher assessment. In this study, whether peer assessment can be adopted in class is considered using FACET analysis. Since this is a regular small English class in Japan, the participants are 18 ESL university students and one teacher. First, one misfitting rater is eliminated and all the other raters including the teacher are included as asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Cheng and Warren (2005) found that peer assessment has been more commonly incorporated into English language writing instruction where peers give feedback to each other's written works. Peer assessment in teaching speaking has also been recognized as being efficient (Luoma, 2004;Matsuno, 2017;Okuda & Otsu, 2010), and it seems to be quite promising to implement in teaching phonetics, a possibility the current research seeks to discover.…”
Section: Peer Assessment In L2 Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng and Warren (2005) found that peer assessment has been more commonly incorporated into English language writing instruction where peers give feedback to each other's written works. Peer assessment in teaching speaking has also been recognized as being efficient (Luoma, 2004;Matsuno, 2017;Okuda & Otsu, 2010), and it seems to be quite promising to implement in teaching phonetics, a possibility the current research seeks to discover.…”
Section: Peer Assessment In L2 Instructionmentioning
confidence: 99%
“…According to Matsuno (2017), assessment is quite a burden for teachers. Especially when they must evaluate their students' oral performances, it may cause some troubles since they can often see those performances only once unless they record them.…”
Section: Benefits Of Peer Assessment In L2 Pronunciation Instructionmentioning
confidence: 99%